2012
DOI: 10.1089/gtmb.2011.0235
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Uptake of Direct-to-Consumer Genetic Testing Among Cancer Cases, Their Relatives, and Controls: The Northwest Cancer Genetics Network

Abstract: Aims: To determine if awareness of, interest in, and use of direct-to-consumer (DTC) genetic testing is greater in a sample of high-risk individuals (cancer cases and their relatives), compared to controls. Methods: Participants were recruited from the Northwest Cancer Genetics Network. A follow-up survey was mailed to participants to assess DTC genetic testing awareness, interest, and use. Results: One thousand two hundred sixty-seven participants responded to the survey. Forty-nine percent of respondents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…This is consistent with other research on genetic testing, which generally showed lower interest in genetic testing among people who identified with a religion [20]. In contrast to previous research, we found no association with education [11,31] or gender [8,11,30].…”
Section: Demographic Factorssupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with other research on genetic testing, which generally showed lower interest in genetic testing among people who identified with a religion [20]. In contrast to previous research, we found no association with education [11,31] or gender [8,11,30].…”
Section: Demographic Factorssupporting
confidence: 90%
“…The items included in the questionnaire were composed based on existing models of behaviour change [9,10], previous literature [11][12][13][14][15][16][17] and expert opinion in the field of genetics, DTC-GT, health education and informed decision-making.…”
Section: Data Collectionmentioning
confidence: 99%
“…We found a high level of awareness about DTC genomics in our study population [23,24,25,26,27], something that can be explained by the media attention that this issue has received in the German-speaking part of Switzerland over the last 2 years. In general, most respondents who were interested in DTC genomics had a natural science/engineering background.…”
Section: Discussionmentioning
confidence: 87%
“…Awareness was significantly higher among the following groups: individuals aged 50–74, college graduates, persons with a regular health care source, those with a prior diagnosis of cancer, Internet users, and urban residents. In a related study, Hall et al [15] compared awareness of DTC-GT between individuals with cancer and their first-degree relatives and an unaffected control group. Among the 1,267 survey respondents, 49% were aware of DTC-GT, with the high-risk group demonstrating a significantly greater level of awareness than controls.…”
Section: Resultsmentioning
confidence: 99%